(untitled) (Research, Society and Development, 2020)
Objective: to identify scientific evidence about rural women’s access to primary health care services. Methodology: this is an integrative literature review, with bibliographic survey carried out in the electronic databases LILACS, MEDLINE and BDEnf via Virtual Health Library from March to April 2020. The descriptors were used: Women’s Health, Zone Rural, Women’s Health and Rural Areas. 59 articles were found, of which 10 met the inclusion and exclusion criteria, being published between the years 2015 and 2019. Results: Most studies were developed in Africa, with five studies, followed by Asia with two, Brazil, Argentina and Bangladesh with one each. The analysis of the data from the integrative review enabled the grouping of studies into two thematic categories: Gestational and puerperal health of women in rural areas and Comprehensive health care for women in rural areas. Conclusion: a gap was found in Brazilian research related to the access of women living in rural areas to primary health care services.